Reformasi Birokrasi Dalam Pelayanan Publik (Studi Pelayanan Terpadu Satu Pintu) - Yusriadi Yusriadi; Misnawati Misnawati (Jurnal Ilmiah Ilmu Administrasi Publik, 2017)
This study aims to identify the implementation of bureaucratic reforms, as well as to offer several solutions for the improvement of licensing administration services. This study used a qualitative approach with the type of instrumental case study research. The location of the research was conducted at Integrated Licensing Service Agency (BP2T) in Kabupaten Bone.Teknik data collection used, namely: in-depth interviews, document studies and observation. Data are analyzed through data reduction stages, data presentation, conclusion and verification. The results showed that the implementation of bureaucratic reform in the administration of licensing services, from the Institutional aspect that the licensing service of Bone Regency has been in the form of One Stop Service; Human Resources aspects that the existing employee qualifications are not in accordance with organizational needs, discipline and responsibilities of employees is still relatively low; aspects of the System and Procedures that generally permits are completed beyond the prescribed timeframe, the existence of discrimination and inconsistency. Through this research, verification of several concepts and theories, namely formalism as one of the characteristics of prismatic society proposed by Fred W Riggs on justified in this study, which in the phenomenon the author calls it by the term "Regulation of the Tongue.